Timing of carbohydrate and protein intake and hydration status of German junior football players - Braun, H.; Bauhaus, H.; Stegemann, S.; Thevis, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Recently, the UEFA expert group highlighted that nutritional support plays a key factor for junior football players and will help to optimise growth, health, performance, recovery, training adaptations and body composition (Colllins et al. 2020). Although, young players may have different nutritional needs from those of adults the expert group stated that carbohydrate (CHO) and protein (PRO) needs are similar to those of senior players and Urine specific gravity (USG) can be a useful indicator of hydration status suggesting euhydration of USG <1.020. Data on nutritional status in junior football players are still rare, therefore this observational study focus, whether academy players follow the UEFA nutrition guidelines on training and match days.